Tanggung Jawab Orang Tua Yang Menelantarkan Anak Prespektif Perdata - Manuhutu, Novrilianty Abril; Laturette, Adonia Ivone; Angga, La Ode (Faculty of Law, Universitas Pattimura, 2024)
Introduction: Government Children are a mandate as well as a gift from God the Almighty, who must always be guarded because every person (child) has basic human rights that have been regulated in the constitution, even he has inherent dignity and human rights, so children cannot be abandoned. The law has regulated related to child protection.Purposes of the Research: The purpose of this study is to find out and explain the responsibilities of parents who abandon children, and the legal consequences for parents who abandon children.Methods of the Research: This research uses the type of normative juridical research, with a problem approach used is descriptive analysis, namely literature studies and from field studies, the sources of law used are primary legal materials and secondary legal materials. The data collection procedure is using literature study. The legal management and analysis used is the method of normative analysis, namely relating it to the applicable legal norms.Results of the Research: The results of the writing show that the responsibility of parents who abandon children is caused by economic factors, harmony in the family, the awareness and attention of parents towards children is so lacking that children lose their rights. The legal consequences for parents who abandon their children are fines, even up to the revocation of custody of their children, therefore supervision regarding this case must be more efficient.